EL FRACCIONAMIENTO TRIBUTARIO DEL CONTRIBUYENTE EN LA MUNICIPALIDAD PROVINCIAL DE TRUJILLO - Lopez Cenizario, Evelyn Natali (2018)
The present project has the intention of defining the situation of the tax authority of the Municipalities and if the extreme application of the tax power in relation to the Tax Fractionation is valid. That is, to determine if the arbitrary decision of the Municipalities to request the cancellation of half of the debt to subsequently grant the Fractionation is valid before what is regulated by the Tax Code on this legal figure. This in order to solve the problem that thousands of taxpayers go through that are frustrated and forced to sell everything due to the fact that the Municipalities do not allow the Fractionation of the tax debt. It is because of these fundamentals that, the present project intends to satisfy a need that has not been dealt with by the Peruvian doctrine and much less by a Law that regulates this situation.